Las microfinanzas y su incidencia en el nivel de pobreza de las personas con discapacidad y sus familias en la parroquia Malacatos, cantón Loja, provincia de Loja, año 2015 - Chamba Sarango, Gabriela Lisseth (2016)
People with disabilities because of their health status or unfounded stereotypes in society, they have greater difficulty to find a job, to get permanent income, to save and to access to products offered by traditional banks, making it difficult to meet their needs and his family, It is causing a worsening of their poverty or extreme poverty. Therefore, the research entitled "Microfinance and its impact on the poverty of people with disabilities and their families in the parish Malacatos, canton Loja, province of Loja, 2015" The main objective was: To determine the presence of microfinance in the Malacatos parish in the province of Loja, 2015, through a descriptive study, with the purpose to establish their impact on the poverty of people with disabilities and their families. In addition, Participants were heads of households of people with disabilities and officials of microfinance institutions in the parish Malacatos. The scientific method was used in the expressions of inductive, deductive, analytical, synthetic and statistical. Also, the techniques used were the bibliographic, the survey and interview with their respective instruments are: bibliographic record, the survey questionnaire and the script of the interview. Finally, the main result in the investigative process was that 100,00% of households of people with disabilities who obtained a microcredit improved their living conditions in areas such as increased economic capacity, improved housing, access to basic services and reducing the level of overcrowding. This also had a positive impact on the poverty level for non-satisfied basic needs (NBI), it was reduced by 9,18 points compared to 2010, poverty stood at 58,16% for 2015.